Is first trimester body mass index of antenatal mothers associated with selected feto-maternal outcomes? - Arora, Chanchal; Thadathil, Smitha; R., Rejani; Sharma, Punita A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Mothers are the creators and sustainers of progeny. The health and wellbeing of children is intimately linked with the health, nutrition, education and well-being of their mothers because she is both the seed as well as the soil where in the baby is nurtured for 9 months. Hence the present study was conducted to determine the association between first trimester body mass index (BMI) of antenatal mothers with the mode of delivery, birth weight and APGAR scores of new born babies at birth in a tertiary care hospital. Methods: A cross-sectional study was conducted amongst 115 antenatal mothers who reported to the Labor room in a tertiary care hospital of Pune during the period of Nov. 2017 to Feb. 2018, to determine the association between first trimester body mass index (BMI) of antenatal mothers with the mode of delivery, birth weight and APGAR scores of new born babies. Results: The findings were suggestive of increased odds of APGAR of <7 at 1 min of birth among new born babies born to the study participants of low BMI group as compared to the new born babies born to the high BMI group; Increased odds of birth weight of >3.5 kg and gestational weight gain of >14 kg and greater odds of complications among new born babies born to the study participants of high BMI group than the new born babies born to the low BMI group. Conclusions: The study concluded that birth weight of the new born babies shows a clinically significant increasing trend in association with the increasing first trimester BMI of their mothers.